Phylattrin, a new cytotoxic xanthone from Calophyllum soulattri - Mah, Siau Hui; Ee, Gwendoline Cheng Lian; Teh, Soek Sin; Rahmani, Mawardi; Lim, Yang Mooi; Go, Rusea (MDPI, 2012)
Our continuing studies on secondary metabolites from the stem bark of Calophyllum soulattri has led to the isolation of another new diprenylated xanthone, phylattrin (1), in addition to five other xanthones and two common sterols. The xanthones are soulattrin (2), caloxanthone C (3), macluraxanthone (4), brasixanthone B (5) and trapezifolixanthone (6) while the sterols are stigmasterol (7) and β-sitosterol (8). The structures of these compounds were determined on the basis of spectroscopic analyses such as 1D and 2D-NMR, HRESIMS, IR and UV. Compounds 1–7 exhibited moderate cytotoxic activities against SNU-1, HeLa, Hep G2, NCI-H23, K562, Raji, LS174T, IMR-32 and SK-MEL-28 cells.